Analisis Strategi Pemasaran dalam Mempertahankan Keberlangsungan Usaha pada Rumah Makan Gemilang Rasa di Kelurahan Talang Bakung Kecamatan Jambi Selatan - Nursamsi, Nursamsi; Addiarahman, Addiarahman; Orinaldi, Mohammad (ARZUSIN, 2024)
Marketing strategy is the operational planning of a company with a design of activities to achieve goals while still taking into account internal and external business factors. Marketing is a strategic effort that aims to maintain and develop a business in order to generate profits for the company in both the goods and services sectors. Business sustainability is a condition that allows a company to survive in a competitive environment. This research aims to determine the marketing strategy of the Gemilang Rasa restaurant in maintaining business continuity and why the Gemilang Rasa restaurant does not carry out an optimal marketing mix, especially in the promotion process. This research uses descriptive qualitative methods. The data collection technique in this research uses observation, interview and documentation techniques. The results of this research show that the marketing strategy used by Gemilang Rasa Restaurant is the 6P Marketing Mix and the reason why Gemilang Rasa Restaurant does not carry out an optimal marketing mix, especially in the promotion process, is a lack of understanding about digitalization and the existence of costs/profit sharing when partnering with online food. delivery. Apart from that, there are also obstacles faced in maintaining business continuity, namely: business competition constraints and instability in raw material prices.